Mile-a-minute (Mikania micrantha): A New Weed in South Florida - Brent Sellers; Ken Langeland (EDIS)
SS-AGR-328, a 2-page illustrated fact sheet by Brent Sellers and Ken Langeland, describes this new weed, a highly branched perennial vine, reported in late 2009 near Homestead FL, and how to identify it and what to do if you find it. Published by the UF Department of Agronomy, January 2010.